A Comparison of Sputum Evaluation Conversion of Pulmonary TB patients with DM and non-DM in High Burden Setting - Rahman, Anita; Subianto, Tantri; Mulyawan, Kadek; Zulkarnaen, Decky Aditya (Malang Respiratory Journal, 2023)
ABSTRACT Background Tuberculosis (TB) remains a global health problem and is one of the leading causes of death worldwide. By 2022, an estimated 10 million people will suffer from TB worldwide. Based on data from the Global Tuberculosis Report in 2022, Indonesia ranks second as a high-burden country in the world after India. An estimated 1.5 million people die from tuberculosis, becoming the 13th leading cause of death worldwide and the second most deadly infectious disease after COVID-19. Currently, many new cases of TB are influenced by several risk factors, one of which is Diabetes Mellitus (DM). Pulmonary TB is a potential opportunistic infection for people with Diabetes Mellitus. TB patients with DM are at risk of sputum conversion failure after TB treatment, 1.69 times higher risk of treatment failure, 1.24 times higher risk of anti-TB drug resistance, 3.89 times higher risk of relapse, and 4.95 times higher risk of death during treatment compared to TB patients. Aim of Study To evaluate the sputum smear conversion results at the end of the second month of treatment of patients with Tuberculosis with Diabetes Mellitus (TB-DM) and Tuberculosis Non-Diabetes Mellitus (TB-NDM). Methods This research was analytical with a retrospective cohort design by taking secondary data from the Tuberculosis Information System (SITB). The data were recorded in SITB and registered as TB patients undergoing Anti-Tuberculosis Drug treatment and screening for Diabetes Mellitus in all districts in West Nusa Tenggara Province in 2022. Results Among 200 patients with TB in this study, male patients dominated 62% of TB patients. TB patients are mostly found in the age group 46-55 years with 28,5%. Generally, TB patients come from Mataram, with an 18% percentage. Most TB patients were diagnosed using GeneXpert (80,5%). The sputum conversion rate at the end intensive phase in TB-DM patients reached 95%, while in TB-NDM patients, only 85%. The comparative test showed a significant difference between the AFB Sputum Evaluation conversion results between TB patients and those without DM (p-value: 0.018, p<0.05). Conclusion There is a significant difference between the AFB Sputum Evaluation conversion results between TB patients and those without DM. Keywords : Diabetes, diabetes mellitus, sputum conversion, tuberculosis, TB, DM